en - Ni Komang Ayu Suardani; Desak Putu Eka Pratiwi; I Wayan Juniartha (Program Magister Linguistik Universitas Udayana, 2022)
Abstract–This research aims at finding out verbal and non-verbal signs and also explaining the meaning of those verbal and visual signs found in the posters of Korean pop idol. The data were taken from ten printed posters of Korean pop idol from the internet. This study used the theory of semiotic by Saussure (1983) to find out the verbal and non-verbal signs and theory meanings by Barthes (1968) to find out the meaning of verbal and visual signs in the posters of Korean pop idol. Descriptive qualitative method was used to analyze the data in this study. As the result, those ten posters of Korean pop idol show the verbal and visual signs that support the agencies to promote their idols. In the verbal and visual signs of the posters album and concert of Korean idol show most all of them conveys connotative meaning. In the non-verbal signs of the advertisements almost all of the posters of Korean idol used the member of the idol group as a model, It means the advertisements want to attract the people interest by using a the good visual of the idol. Keyword: semiotic; verbal signs; non-verbal signs; korean album poster & concert poster